INOVASI MEDIA PEMBELAJARAN WORDWALL BERBASIS QUIZIZZ : ALTERNATIF DALAM MENINGKATKAN CRITICAL THINGKING SISWA DI ERA ABAD 21 - Akhmad Dalil Rohman; Tri Noor Khaliza (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
21st-century education demands that educators align teaching methods with the development of students, particularly in aspects such as critical thinking, communication, collaboration, and creative skills. Integrating technology into learning is considered a solution, with educational media like Wordwall based on Quizizz being one alternative. This media not only aids teachers in delivering material but also enriches student creativity and enhances their concentration in the learning process. However, the limitation of technological facilities in some schools leads to the use of less effective lecture methods. This study employs a library research method to explore the effectiveness of Wordwall based on Quizizz in enhancing students' critical thinking skills. Data were collected from various literature sources, including scientific journals, books, and articles. Data analysis was conducted descriptively by reviewing and synthesizing findings from existing literature. The results of the study indicate that the implementation of Wordwall based on Quizizz significantly improves students' critical thinking skills. This interactive learning media can provide various engaging and challenging learning activities that encourage students to think logically and analytically. Moreover, real-time feedback from Quizizz helps students quickly evaluate and improve their understanding. However, challenges such as the technological access gap and the need for teacher training must be addressed to ensure optimal implementation.